Analysis of the communication of antibiotic resistance in the digital press of Spain. Effect of the approval of the National Plan of Antibiotic Resistance - Jimenez Sarmiento, Mercedes (Revista Española de Comunicación en Salud, 2020)
Introduction: Antibiotic resistance and the emergence of resistant bacteria have been cataloged as a global public health threat by the World Health Organization (WHO) and the European Union. The article that is presented shows a study on the informative coverage in digital media of this matter. Objective: To analyze the coverage presence of antibiotic resistance in digital media. Methods: This descriptive study quantifies the number of news appearing in four media, El País, El Mundo, ABC and 20 minutes before and after the approval in 2014 of the National Antibiotic Resistance Plan. Results: The results showed an unequal treatment according to the number of informative pieces in the four digital newspapers but on the rise since the approval of the plan. Conclusions: The informative treatment of antibiotic resistance according to the number of quantified news is increasing every year although unevenly in each medium.
Keywords: resistance; antibiotics; coverage; digital media